2014
DOI: 10.1159/000363005
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Thymosin �4 Promotes the Proliferation, Migration, and Activation of Human Hepatic Stellate Cells

Abstract: Background & Aims: It has recently been reported that thymosin beta-4 (Tβ4) has anti-fibrogenic effects in human hepatic stellate cells (HSCs) in vitro, but the mechanisms underlying these effects remain unclear. The aim of this study was to investigate the roles of Tβ4 in the proliferation, migration, and activation of HSCs. Methods: Enzyme-linked immunosorbent assays (ELISA), immunohistochemistry, and western blot assays were utilized to determine the expression levels of Tβ4 in serum, liver tissues, and LX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 41 publications
(54 reference statements)
1
48
0
Order By: Relevance
“…It is well known that activated hepatic stellate cells (HSCs), playing a pivotal role in the development of liver fibrosis, are mainly responsible for the excessive accumulation of ECM proteins in the liver [4]. Generally, HSCs are quiescent in the normal liver.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that activated hepatic stellate cells (HSCs), playing a pivotal role in the development of liver fibrosis, are mainly responsible for the excessive accumulation of ECM proteins in the liver [4]. Generally, HSCs are quiescent in the normal liver.…”
Section: Introductionmentioning
confidence: 99%
“…In response to chronic liver injury, hepatic stellate cells (HSCs) are activated and differentiate into myofibroblast-like cells, and express abundant alpha smooth muscle actin (α-SMA) and extracellular matrix components [1,2]. Therefore, the activation and proliferation of HSCs are central events in the progression of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tβ4 is the major G-actin-sequestering molecule with diverse functions related to cell proliferation, migration, angiogenesis, cell survival, and inhibition of inflammation [4][5][6][7]. Multiple studies have indicated that Tβ4 protein may promote tissue regeneration in multiple processes including corneal, epidermal, and cardiac wound healing, and is also effective in inflammatory diseases including severe acute pancreatitis and bleomycininduced lung fibrosis [8].…”
Section: Introductionmentioning
confidence: 99%